An Immersive Virtual Reality System For Practicum Chair Assembly Training To Increase Effectiveness of PPTI 2 - Vani Aditiya Nur Huda; Susy Susmartini; Lobes Herdiman (Jurnal Ilmiah Teknik Industri, 2022)
The implementation of practicum chair assembly training in PPTI 2 still uses conventional method training. The use of conventional methods has some drawbacks including high resource requirements when starting out and requires an experienced coach who should always be there whenever there is training. The use of conventional methods in the training of practicum chair assembly is considered less effective. There needs to be other alternatives in practicum chair assembly training. The alternative chosen is training using Virtual reality (VR).  This paper contains a comparison between training using conventional methods and using virtual reality. That proves training uses VR more effectively than training with conventional methods.